Validade da formação da auxiliar odontológica em Londrina - Souza, Lizete Leitão de; Lino, Hélion Leão (Semina: Ciências Agrárias, 1983)
The present work aimed to evaluate the importance of the training of dental auxiliaries through a specific course. The study involved a significant sample of dentists of the city of Londrina which were interviewed with the help of a questionnaire that, among some other itens, inquired about the objective of the training and the usefulness of the dental auxiliaries in Odontology. The questionnaire also collected material for the improvement of the program of a Formation Especial Course for Dental Auxiliaries of the Fundação Universidade Estadual de Londrina. The interviewed dentists seemed to agree with the fact of having dental auxiliaries in offices as well as with the formation of these auxiliaries through especiftc courses.